Electric de-intercalation and extraction lithium pole plate as well as preparation method and application thereof
By coating the electrode plate with a conductive undercoat and a porous electrode slurry layer, the problem of poor electronic conductivity was solved, achieving a highly efficient and stable lithium extraction process and improving the physical stability and energy density of the electrode plate.
Patent Information
- Application Number
- CN202511152606.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-18
- Publication Date
- 2025-11-14
AI Technical Summary
Existing electrode plates for lithium extraction and deintercalation have poor electronic conductivity, resulting in low lithium extraction efficiency and poor stability.
The structure design employs a modified current collector and a porous electrode slurry layer. By coating the surface of the porous current collector substrate with a conductive primer and a porous electrode slurry layer, the electronic conductivity and stability are improved.
It significantly improves lithium extraction efficiency and the physical stability of the electrode, enhances the electronic and ion conduction capabilities of the electrode, extends the electrode life, and improves energy density and lithium extraction efficiency.
Smart Images

Figure CN120945194A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium extraction technology, and specifically relates to an electro-deintercalation lithium extraction electrode plate, its preparation method, and its application. Background Technology
[0002] Electro-deintercalation lithium extraction, as an emerging lithium resource extraction technology, offers advantages over existing lithium extraction techniques, including being environmentally friendly, having low energy consumption, and minimizing electrode material loss. Its principle utilizes Li... + The electrochemical differences between the electrode and other coexisting ions allow for selective insertion / extraction of Li by controlling the potential. + However, due to the poor electronic conductivity of the electrode plates used in the current lithium extraction technology, existing lithium extraction methods suffer from problems such as low lithium extraction efficiency and poor stability. Summary of the Invention
[0003] This invention aims to at least solve one of the technical problems existing in related technologies. To this end, this invention proposes an electro-extraction lithium electrode plate, its preparation method, and its application. This electro-extraction lithium electrode plate has good electronic conductivity and can significantly improve lithium extraction efficiency and stability.
[0004] The above-mentioned technical objective of the present invention is achieved through the following technical solution: An electrolytically extracted lithium electrode plate includes: a modified current collector comprising a porous current collector substrate and a conductive undercoating, wherein the conductive undercoating is disposed on the surface of the porous current collector substrate; and a porous electrode slurry layer disposed on the surface of the modified current collector.
[0005] In one embodiment, the porous current collector substrate is at least one of ruthenium-iridium-plated titanium mesh, titanium mesh, porous graphite plate, and porous graphite felt.
[0006] In one embodiment, the conductive base coating is formed by coating and drying a conductive base coating slurry, the conductive base coating slurry comprising the following components: a conductive solution, a first conductive agent, a first binder, a dispersant, and a first solvent.
[0007] In one embodiment, the thickness of the conductive undercoat is 0.4-0.6 mm.
[0008] In one embodiment, the amount of the conductive undercoat is 2%-5% of the weight of the porous current collector substrate.
[0009] In one embodiment, the conductive primer slurry comprises the following components in parts by weight: conductive solution: 30.7-65.8 parts, first conductive agent: 24.6-60.2 parts, first binder: 4.9-10.1 parts, dispersant: 1.5-4.3 parts, wherein the first solvent is used to adjust the solid content of the conductive primer slurry, and the solid content of the conductive primer slurry is 3.5%-11.8%.
[0010] In one embodiment, the conductive primer slurry is prepared by mixing a dispersant with a first solvent, then adding a conductive solution and a first binder and mixing, and finally adding a first conductive agent and mixing, thus obtaining the final product.
[0011] In one embodiment, the conductive solution comprises a carbon nanotube solution with a solid content of 3%-10%. The carbon nanotubes in the carbon nanotube solution are multi-walled carbon nanotubes with a diameter of 10-50 nm.
[0012] In one embodiment, the first conductive agent includes at least one of conductive carbon SP, conductive graphite KS-6, and Ketjen black.
[0013] In one embodiment, the first adhesive includes at least one of polyvinylidene fluoride, VW770 adhesive, and HSV900 adhesive.
[0014] In one embodiment, the dispersant includes at least one of sodium carboxymethyl cellulose, sodium hydroxypropyl methyl cellulose, and methyl cellulose.
[0015] In one embodiment, the first solvent is N-methylpyrrolidone.
[0016] In one embodiment, the porous electrode slurry layer is formed by coating with a porous electrode slurry, which includes the following components: a second solvent, an active material, a hydrophilic agent, a second conductive agent, a second binder, a structuring agent, and a pore-forming agent.
[0017] In one embodiment, the porous electrode slurry comprises the following components in parts by weight: active material: 67.5-85.7 parts, hydrophilic agent: 2.8-10.1 parts, second conductive agent: 4.3-10.5 parts, second binder: 4.0-10.6 parts, structural agent: 1.2-3.5 parts; second solvent: 90-130 parts, pore-forming agent: 10.5-40.9 parts.
[0018] In one embodiment, the porous electrode paste is prepared by first mixing a second binder with a second solvent to obtain a slurry, and then adding a hydrophilic agent, a second conductive agent, an active material, a structural agent, and a pore-forming agent to the slurry and mixing them to obtain the paste.
[0019] In one embodiment, the active material includes at least one of lithium iron phosphate, lithium manganese oxide, and lithium manganese iron phosphate.
[0020] In one embodiment, the second conductive agent includes at least one of conductive carbon SP, conductive graphite KS-6, Ketjen black, and carbon nanotubes.
[0021] In one embodiment, the second adhesive includes at least one of polyvinylidene fluoride, VW770 adhesive, and HSV900 adhesive.
[0022] In one embodiment, the hydrophilic agent includes at least one of polyethylene glycol, polydopamine, chitosan, and polyvinyl alcohol.
[0023] In one embodiment, the structural agent comprises carbon fiber.
[0024] In one embodiment, the second solvent comprises N-methylpyrrolidone.
[0025] In one embodiment, the pore-forming agent includes at least one of sodium chloride and ammonium bicarbonate.
[0026] A method for preparing an electrode plate for electro-deintercalation and extraction of lithium as described above includes the following steps: (1) Apply conductive primer slurry to the surface of the porous current collector substrate and dry it to form a conductive primer coating on the surface of the porous current collector substrate, thereby obtaining a modified current collector. (2) Coat the surface of the modified current collector with the porous electrode paste and dry it.
[0027] In one embodiment, in step (1), the drying temperature is 60-80°C and the drying time is 6-10 hours.
[0028] In one embodiment, in step (2), the drying is first done at 45-60°C for 3-5 hours, and then at 80-95°C for 4-8 hours.
[0029] An electro-deintercalation lithium extraction device includes an electro-deintercalation lithium extraction electrode plate as described above.
[0030] The beneficial effects of this invention are: (1) Compared with the prior art, the present invention uses conductive base coating slurry to modify the current collector to conduct electricity, thereby significantly reducing the resistance and impedance of the electrode plate, reducing the plateau voltage of the electrode plate, reducing polarization, improving the electronic and ion conduction inside the electrode plate coating, thereby enhancing the electrochemical performance; in addition, it can improve the situation where the electrode plate specific capacity is not fully utilized due to excessive coating thickness, and improve the energy density and lithium extraction efficiency of the electrode plate.
[0031] (2) Compared with the prior art, the present invention uses conductive base coating slurry to modify the surface roughness of the current collector, which enhances the bonding tightness between the modified current collector and the porous electrode slurry layer, thereby greatly improving the shear force of the electrode plate, improving the physical strength and physical stability of the electrode plate, greatly improving the cycle performance of the electrode plate, and extending the life of the electrode plate. Attached Figure Description
[0032] Figure 1 The images show the unmodified current collector and the modified current collector in Embodiment 1 of the present invention. Figure 2 The EIS impedance spectra of Embodiment 1 and Comparative Example 1 of the present invention are shown. Detailed Implementation
[0033] The present invention will be further described below with reference to specific embodiments.
[0034] Example 1: A method for manufacturing an electrolytically extracted lithium electrode plate includes the following steps: (1) Preparation of modified current collectors: Preparation of conductive primer slurry: Sodium carboxymethyl cellulose was dissolved in N-methylpyrrolidone and stirred for 20 min to prepare sodium carboxymethyl cellulose solution. Carbon nanotube solution and polyvinylidene fluoride were poured into sodium carboxymethyl cellulose solution and premixed at 800 rpm for 1 min in a high-speed mixer, then stirred at 2000 rpm for 20 min. Finally, conductive carbon SP was added, and premixed at 800 rpm for 1 min in a high-speed mixer, then stirred at 2000 rpm for 20 min to prepare conductive primer slurry. The weight parts of each component of conductive primer slurry are: 2.1 parts sodium carboxymethyl cellulose, 43.6 parts carbon nanotube solution (solid content 5%), 6.2 parts polyvinylidene fluoride, and 48.1 parts conductive carbon SP. N-methylpyrrolidone was used to adjust the solid content of conductive primer slurry. The solid content of the prepared conductive primer slurry is 7.2%. The carbon nanotubes in the carbon nanotube solution are multi-walled carbon nanotubes with a diameter of 10-50 nm. Take a clean and dry titanium mesh ( Figure 1 The unmodified current collector (in the case of a titanium mesh) was prepared by uniformly applying a conductive primer slurry to the surface of the titanium mesh using a small spatula, ensuring that the slurry could penetrate into the gaps in the mesh and that the surface was smooth without obvious protrusions or agglomerations. The mesh was then baked in a 65°C oven for 8 hours to form a conductive primer coating with a thickness of 0.5 mm and a coating weight of 3% of the titanium mesh. Figure 1 (modified current collector in the middle). (2) Preparation of porous electrode paste: First, polyvinylidene fluoride (PVDF) was added to the solvent N-methylpyrrolidone and stirred to dissolve and prepare a gel. Then, polyethylene glycol, conductive carbon SP, lithium iron phosphate, and carbon fiber were dry-mixed and added to the prepared gel. The mixture was stirred for 4 hours. Finally, NaCl was added and stirred for 30 minutes. After mixing evenly, a porous electrode slurry was prepared. The weight parts of each component of the porous electrode slurry were: 5.7 parts PVDF, 78.8 parts lithium iron phosphate, 4.5 parts polyethylene glycol, 9.5 parts conductive carbon SP, 1.5 parts carbon fiber, 110 parts N-methylpyrrolidone, and 16.1 parts NaCl. The lithium vacancy rate of the main material, lithium iron phosphate, was 40%.
[0035] (3) Preparation of lithium electrode plates for electro-deintercalation and extraction: A porous electrode slurry was coated on both sides of the modified current collector using a 1 mm thick coating mold. The coating thickness was consistent with that of the coating mold. After coating, the plate was baked at a low temperature of 52℃ for 4 hours and then at a high temperature of 90℃ for 6 hours. After the plate was dried, it was placed in 500 ml of water and stirred and soaked for 12 hours to dissolve NaCl, thereby forming a porous electrode slurry layer on the surface of the modified current collector, thus preparing a porous electrode plate for lithium extraction and insertion.
[0036] Example 2: A method for fabricating an electrode plate for electro-deintercalation and extraction of lithium. The steps are the same as in Example 1, except that the weight parts of each component in the conductive primer slurry are: 2.1 parts sodium carboxymethyl cellulose, 31.5 parts carbon nanotube solution (solid content 5%), 6.2 parts polyvinylidene fluoride, and 60.2 parts conductive carbon SP. The solid content of the prepared conductive primer slurry is 11.8%.
[0037] Example 3: A method for fabricating an electrode plate for electro-deintercalation and extraction of lithium. The steps are the same as in Example 1, except that the weight proportions of each component in the conductive primer slurry are: 2.1 parts sodium carboxymethyl cellulose, 65.8 parts carbon nanotube solution (solid content 5%), 6.2 parts polyvinylidene fluoride, and 25.9 parts conductive carbon SP. The solid content of the prepared conductive primer slurry is 4.5%. Example 4: A method for manufacturing an electrolytically extracted lithium electrode plate includes the following steps: (1) Preparation of modified current collectors: Preparation of conductive primer slurry: Sodium carboxymethyl cellulose was dissolved in N-methylpyrrolidone and stirred for 20 min to prepare sodium carboxymethyl cellulose solution. Carbon nanotube solution and polyvinylidene fluoride were poured into sodium carboxymethyl cellulose solution and premixed at 800 rpm for 1 min in a high-speed mixer, then stirred at 2000 rpm for 20 min. Finally, conductive carbon SP was added, and premixed at 800 rpm for 1 min in a high-speed mixer, then stirred at 2000 rpm for 20 min to prepare conductive primer slurry. The weight parts of each component of conductive primer slurry are: 2.1 parts sodium carboxymethyl cellulose, 43.6 parts carbon nanotube solution (solid content 5%), 6.2 parts polyvinylidene fluoride, and 48.1 parts conductive carbon SP. N-methylpyrrolidone was used to adjust the solid content of conductive primer slurry. The solid content of the prepared conductive primer slurry is 7.2%. The carbon nanotubes in the carbon nanotube solution are multi-walled carbon nanotubes with a diameter of 10-50 nm. Take a clean and dry titanium mesh, and use a small flat spatula to evenly scrape the conductive primer slurry onto the surface of the titanium mesh, ensuring that it can penetrate into the gaps in the titanium mesh and that the surface is flat without obvious protrusions or agglomeration. Then bake it in a 65℃ oven for 8 hours to form a conductive primer coating on the surface of the titanium mesh. The thickness of the conductive primer coating is 0.5 mm, and the coating amount is 3% of the weight of the titanium mesh, thereby preparing the modified current collector. (2) Preparation of porous electrode paste: First, polyvinylidene fluoride (PVDF) was added to the solvent N-methylpyrrolidone and stirred to dissolve and prepare a gel. Then, polyethylene glycol, conductive carbon SP, lithium iron phosphate, and carbon fiber were dry-mixed and added to the prepared gel. The mixture was stirred for 4 hours. Finally, NaCl was added and stirred for 30 minutes. After mixing evenly, a porous electrode slurry was prepared. The weight parts of each component of the porous electrode slurry were: 5.7 parts PVDF, 78.8 parts lithium iron phosphate, 4.5 parts polyethylene glycol, 9.5 parts conductive carbon SP, 1.5 parts carbon fiber, 110 parts N-methylpyrrolidone, and 16.1 parts NaCl. The lithium vacancy rate of the main material, lithium iron phosphate, was 40%.
[0038] (3) Preparation of lithium electrode plates for electro-deintercalation and extraction: A porous electrode slurry was coated on both sides of the modified current collector using a 2mm thick coating mold. The coating thickness was consistent with that of the coating mold. After coating, the plate was baked at a low temperature of 52℃ for 4 hours and then at a high temperature of 90℃ for 6 hours. After the plate was dried, it was placed in 500ml of water and stirred and soaked for 12 hours to dissolve NaCl, thereby forming a porous electrode slurry layer on the surface of the modified current collector, thus preparing a porous electrode plate for lithium extraction and insertion.
[0039] Example 5: A method for manufacturing an electrolytically extracted lithium electrode plate includes the following steps: (1) Preparation of modified current collectors: Preparation of conductive primer slurry: Sodium carboxymethyl cellulose was dissolved in N-methylpyrrolidone and stirred for 20 min to prepare sodium carboxymethyl cellulose solution. Carbon nanotube solution and polyvinylidene fluoride were poured into sodium carboxymethyl cellulose solution and premixed in a high-speed mixer at 800 rpm for 1 min, and then stirred at 2000 rpm for 20 min to prepare conductive primer slurry. The weight parts of each component are: 2.5 parts sodium carboxymethyl cellulose, 91.8 parts carbon nanotube solution (solid content 5%), 5.7 parts polyvinylidene fluoride, and N-methylpyrrolidone is used to adjust the solid content of conductive primer slurry. The solid content of the prepared conductive primer slurry is 5%. The carbon nanotubes in the carbon nanotube solution are multi-walled carbon nanotubes with a diameter of 10-50 nm. Take a clean and dry titanium mesh, and use a small flat spatula to evenly apply the conductive primer slurry to the surface of the titanium mesh, ensuring that it can penetrate into the gaps in the titanium mesh and that the surface is smooth without obvious protrusions or agglomerations. Then bake it in a 65℃ oven for 8 hours to form a conductive primer coating on the surface of the titanium mesh. The modified current collector conductive primer coating is 0.5 mm thick and the coating amount is 3% of the weight of the titanium mesh. (2) Preparation of porous electrode paste: First, polyvinylidene fluoride (PVDF) was added to the solvent N-methylpyrrolidone and stirred to dissolve and prepare a gel. Then, polyethylene glycol, conductive carbon SP, lithium iron phosphate, and carbon fiber were dry-mixed and added to the prepared gel. The mixture was stirred for 4 hours. Finally, NaCl was added and stirred for 30 minutes. After mixing evenly, a porous electrode slurry was prepared. The weight parts of each component of the porous electrode slurry were: 5.7 parts PVDF, 78.8 parts lithium iron phosphate, 4.5 parts polyethylene glycol, 9.5 parts conductive carbon SP, 1.5 parts carbon fiber, 110 parts N-methylpyrrolidone, and 16.1 parts NaCl. The lithium vacancy rate of the main material, lithium iron phosphate, was 40%.
[0040] (3) Preparation of lithium electrode plates for electro-deintercalation and extraction: A porous electrode slurry was coated on both sides of the modified current collector using a 1 mm thick coating mold. The coating thickness was consistent with that of the coating mold. After coating, the plate was baked at a low temperature of 52℃ for 4 hours and then at a high temperature of 90℃ for 6 hours. After the plate was dried, it was placed in 500 ml of water and stirred and soaked for 12 hours to dissolve NaCl, thereby forming a porous electrode slurry layer on the surface of the modified current collector, thus preparing a porous electrode plate for lithium extraction and insertion.
[0041] Example 6: A method for manufacturing an electrolytically extracted lithium electrode plate includes the following steps: (1) Preparation of modified current collectors: Preparation of conductive primer slurry: Sodium carboxymethyl cellulose was dissolved in N-methylpyrrolidone and stirred for 20 min to prepare a sodium carboxymethyl cellulose solution. Polyvinylidene fluoride was poured into the sodium carboxymethyl cellulose solution and premixed at 800 rpm for 1 min in a high-speed mixer, then stirred at 2000 rpm for 20 min. Finally, conductive carbon SP was added, and the mixture was premixed at 800 rpm for 1 min in a high-speed mixer, then stirred at 2000 rpm for 20 min to prepare the conductive primer slurry. The weight parts of each component of the conductive primer slurry were: 4.0 parts sodium carboxymethyl cellulose, 87.1 parts conductive carbon SP, and 8.9 parts polyvinylidene fluoride. N-methylpyrrolidone was used to adjust the solid content of the conductive primer slurry. The solid content of the prepared conductive primer slurry was 5%. The carbon nanotubes in the carbon nanotube solution were multi-walled carbon nanotubes with a diameter of 10-50 nm. Take a clean and dry titanium mesh, and use a small flat spatula to evenly apply the conductive primer slurry to the surface of the titanium mesh, ensuring that it can penetrate into the gaps in the titanium mesh and that the surface is smooth without obvious protrusions or agglomerations. Then bake it in a 65℃ oven for 8 hours to form a conductive primer coating on the surface of the titanium mesh, thereby preparing the modified current collector. The thickness of the conductive primer coating is 0.5 mm, and the coating amount is 3% of the weight of the titanium mesh. (2) Preparation of porous electrode paste: First, polyvinylidene fluoride (PVDF) is added to the solvent N-methylpyrrolidone and stirred to dissolve and prepare a slurry. Then, polyethylene glycol, conductive carbon SP, lithium iron phosphate, and carbon fiber are dry-mixed and added to the prepared slurry after uniform mixing. The mixture is stirred for 4 hours. Finally, NaCl is added and stirred for 30 minutes. After uniform mixing, a slurry coating is prepared. The weight parts of each component of the porous electrode slurry are: 5.7 parts PVDF, 78.8 parts lithium iron phosphate, 4.5 parts polyethylene glycol, 9.5 parts conductive carbon SP, 1.5 parts carbon fiber, 110 parts N-methylpyrrolidone, and 16.1 parts NaCl. The lithium vacancy rate of the main material, lithium iron phosphate, is 40%.
[0042] (3) Preparation of lithium electrode plates for electro-deintercalation and extraction: A porous electrode slurry was coated on both sides of the modified current collector using a 1 mm thick coating mold. The coating thickness was consistent with that of the coating mold. After coating, the plate was baked at a low temperature of 52℃ for 4 hours and then at a high temperature of 90℃ for 6 hours. After the plate was dried, it was placed in 500 ml of water and stirred and soaked for 12 hours to dissolve NaCl, thereby forming a porous electrode slurry layer on the surface of the modified current collector, thus preparing a porous electrode plate for lithium extraction and insertion.
[0043] Comparative Example 1: (The difference from Example 1 is that the current collector is not modified) A method for manufacturing an electrolytically extracted lithium electrode plate includes the following steps: (1) Preparation of porous electrode paste: First, polyvinylidene fluoride (PVDF) was added to the solvent N-methylpyrrolidone and stirred to dissolve and prepare a gel. Then, polyethylene glycol, conductive carbon SP, lithium iron phosphate, and carbon fiber were dry-mixed and added to the prepared gel. The mixture was stirred for 4 hours. Finally, NaCl was added and stirred for 30 minutes. After mixing evenly, a porous electrode slurry was prepared. The weight parts of each component of the porous electrode slurry were: 5.7 parts PVDF, 78.8 parts lithium iron phosphate, 4.5 parts polyethylene glycol, 9.5 parts conductive carbon SP, 1.5 parts carbon fiber, 110 parts N-methylpyrrolidone, and 16.1 parts NaCl. The lithium vacancy rate of the main material, lithium iron phosphate, was 40%.
[0044] (2) Preparation of lithium electrode plates for electro-deintercalation and extraction: A 1mm thick coating mold was used to coat both sides of a titanium mesh (current collector), with the coating thickness consistent with the mold. After coating, the mesh was baked at a low temperature of 52℃ for 4 hours, followed by a high temperature of 90℃ for 6 hours. After drying, the electrode plate was placed in 500ml of water and stirred for 12 hours to dissolve NaCl, thereby forming a porous electrode slurry layer on the surface of the current collector, thus preparing a porous electrode plate for lithium extraction and insertion.
[0045] Comparative Example 2: (The difference from Example 4 is that the current collector is not modified) A method for manufacturing an electrolytically extracted lithium electrode plate includes the following steps: (1) Preparation of porous electrode paste: First, polyvinylidene fluoride (PVDF) was added to the solvent N-methylpyrrolidone and stirred to dissolve and prepare a gel. Then, polyethylene glycol, conductive carbon SP, lithium iron phosphate, and carbon fiber were dry-mixed and added to the prepared gel. The mixture was stirred for 4 hours. Finally, NaCl was added and stirred for 30 minutes. After mixing evenly, a porous electrode slurry was prepared. The weight parts of each component of the porous electrode slurry were: 5.7 parts PVDF, 78.8 parts lithium iron phosphate, 4.5 parts polyethylene glycol, 9.5 parts conductive carbon SP, 1.5 parts carbon fiber, 110 parts N-methylpyrrolidone, and 16.1 parts NaCl. The lithium vacancy rate of the main material, lithium iron phosphate, was 40%.
[0046] (2) Preparation of lithium electrode plates for electro-deintercalation and extraction: A porous electrode slurry was coated on both sides of a titanium mesh (current collector) using a 2mm thick coating mold. The coating thickness was consistent with that of the coating mold. After coating, the electrode was baked at a low temperature of 52℃ for 4 hours and then at a high temperature of 90℃ for 6 hours. After the electrode was dried, it was placed in 500ml of water and stirred and soaked for 12 hours to dissolve NaCl, thereby forming a porous electrode slurry layer on the surface of the current collector, thus preparing a porous electrode plate for lithium extraction and insertion.
[0047] Performance testing: The shear force, resistance, electrochemical performance, and lithium extraction efficiency of the lithium extraction electrodes prepared in Examples 1-6 and Comparative Examples 1-2 were evaluated, specifically including the following steps: (1) Shear force test Shear force was tested using a servo-controlled tensile testing machine SC-8010. One side of a 9*9mm blue double-sided adhesive tape was attached to the glass plate, and the other side was attached to the center of the electrode plate. After fixing it on the tensile testing machine fixture, a tensile test was performed, and the stable value was taken as the electrode plate shear force. (2) Resistance test The resistance of the plate was measured using a RM3544 resistance meter from HIOKI Electric Co., Ltd. The positive terminal of the resistance meter was clamped to the low-resistance current collector tab, and the negative terminal was clamped to the coating. The average value of the resistance data measured at 4 to 6 points was taken as the resistance of the plate.
[0048] (3) Electrochemical performance testing The electrochemical performance of the plates was measured using the Wuhan Landian Battery Testing System CT3002K. The positive and negative electrode clips of Landian were clamped onto the plate tabs for testing. The rate test steps were 0.1C / 0.2C / 0.5C twice each, and the cycle test step was a long cycle test at 0.2C.
[0049] (4) Lithium extraction efficiency test The specific capacity of the plates at 0.1C was measured using the Wuhan Landian Battery Testing System CT3002K. The theoretical lithium extraction efficiency of the plates was calculated based on their average specific capacity. During testing, the plates were assembled into the brine solution of an electro-deintercalation lithium extraction device, ensuring the brine completely submerged the plate coating and that the plates were on the same horizontal plane. Finally, the positive and negative electrodes of the Landian testing system were clamped to the glass slide electrode clamp tabs, and the rate and cycle test program were set in the Landian testing software to begin the test.
[0050] (1) The shear force of the test examples 1-4 and comparative examples 1-2 was used to characterize the physical stability of the plates, the resistance was used to characterize the electronic conduction of the plates, and the impedance was used to characterize the ion conduction of the plates. Then, the rate performance and cycle performance were tested using the Blue Electric charge and discharge cabinet to compare the electrochemical performance and lithium extraction efficiency.
[0051] (2) The results of resistance, rate performance, and cycle performance are shown in Table 1 below. The EIS impedance spectra of Example 1 and Comparative Example 1 are shown below. Figure 2 As shown.
[0052] Table 1. Performance Test Results
[0053] As shown in Table 1, the shear force of the electrode plate for lithium extraction and intercalation described in this specification can reach above 0.33 MPa, the resistivity is not higher than 81.7 mΩ, the capacity retention at 0.2C / 0.1C can reach 87.9% or higher, the capacity retention at 0.5C / 0.1C can reach 51.1% or higher, the capacity retention at 0.2C and 100cls can reach 90.6% or higher, and the lithium extraction efficiency can reach 14.0 mg / m³. 2 / h.
[0054] Comparing Example 1 with Comparative Example 1, and Comparing Example 4 with Comparative Example 2, it can be seen that the electrode plate for lithium extraction using the present invention can enhance the physical stability of the electrode plate by modifying the current collector with a base coating, thereby extending the electrode plate life. By reducing the electrode plate resistance and impedance, the electrode plate has strong electronic conduction and ion transport capabilities, thus exhibiting excellent rate performance and cycle performance, and improving lithium extraction efficiency. At the same time, the electrode plate for lithium extraction modified with a base coating still has high conductivity and good electrochemical performance even after increasing the coating thickness, which improves the situation where the electrode plate capacity is not fully utilized due to excessive coating thickness, and improves the energy density and lithium extraction efficiency of the electrode plate.
[0055] Comparing Examples 1 and 2-3, it can be seen that the conductive solution and conductive agent in the current collector modified primer slurry of the present invention, within a certain usage ratio range, are more beneficial to the physical stability and electrochemical performance of the electrode plate. Comparing Examples 1 and 5-6, it can be seen that the conductive solution and conductive agent in the current collector modified primer slurry of the present invention need to be used in combination to achieve better results. If one of them is used alone, the effect will be worse.
[0056] Depend on Figure 2 It can be seen that modifying the conductivity of the current collector significantly reduces the electrochemical resistance of the electrode, decreases polarization, and improves the electronic conduction of the electrode, which is beneficial to enhancing the lithium extraction capability of the electrode.
Claims
1. An electrode plate for electro-deintercalation and extraction of lithium, characterized in that: include: A modified current collector includes a porous current collector substrate and a conductive undercoat, wherein the conductive undercoat is disposed on the surface of the porous current collector substrate; A porous electrode slurry layer is disposed on the surface of the modified current collector.
2. The electrode plate for electro-deintercalation and extraction of lithium according to claim 1, characterized in that: The porous current collector substrate is at least one of ruthenium-iridium-plated titanium mesh, titanium mesh, porous graphite plate, and porous graphite felt.
3. The electrode plate for electro-deintercalation and extraction of lithium according to claim 1, characterized in that: The conductive base coating is formed by coating and drying a conductive base coating slurry, which includes the following components: a conductive solution, a first conductive agent, a first binder, a dispersant, and a first solvent.
4. The electrode plate for electro-deintercalation and extraction of lithium according to claim 3, characterized in that: The conductive solution comprises a carbon nanotube solution with a solid content of 3%-10%.
5. The electrode plate for electro-deintercalation and extraction of lithium according to claim 3, characterized in that: The first conductive agent includes at least one of conductive carbon SP, conductive graphite KS-6, and Ketjen black.
6. The electrode plate for electro-deintercalation and extraction of lithium according to claim 1, characterized in that: The porous electrode slurry layer is formed by coating with a porous electrode slurry, which includes the following components: a second solvent, an active material, a hydrophilic agent, a second conductive agent, a second binder, a structural agent, and a pore-forming agent.
7. The electrode plate for electro-deintercalation and extraction of lithium according to claim 6, characterized in that: The active material includes at least one of lithium iron phosphate, lithium manganese oxide, and lithium manganese iron phosphate.
8. The electrode plate for electro-deintercalation and extraction of lithium according to claim 6, characterized in that: The second conductive agent includes at least one of conductive carbon SP, conductive graphite KS-6, Ketjen black, and carbon nanotubes.
9. A method for preparing an electro-deintercalation / intercalation lithium electrode plate as described in any one of claims 1 to 8, characterized in that: Includes the following steps: (1) Apply conductive primer slurry to the surface of the porous current collector substrate and dry it to form a conductive primer coating on the surface of the porous current collector substrate, thereby obtaining a modified current collector. (2) Coat the surface of the modified current collector with the porous electrode paste and dry it.
10. An electro-deintercalation and extraction device for lithium, characterized in that: Includes the electro-deintercalation lithium electrode plate according to any one of claims 1 to 8.
Citation Information
Cited By
Granular electrode for extracting lithium as well as preparation method and application of granular electrode
CN121320730A